3. Nachtrag zur Revision der Gattung Infurcitinea Spuler, 1910 (Lepidoptera: Tineidae). - Gaedike, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 1997)
The two new species hellenica and vanderwolfi are described. The female genitalia of captans Gozmany and grisea Petersen are illustrated for the first time and improved drawings of the genitalia of maura and banatica are presented. The species juliae Satschkov is synonymized with tauridella Petersen, and the subgenus Pseudorumelis Satschkov with Infurcitinea. Some new records and corrections of publication dates for some species are given. A catalogue of the known 72 species of the genus is presented including data on their present distribution. Keywords Lepidoptera, Tineidae, Infurcitinea Spuler, new species, Catalogue. Nomenclatural Acts hellenica Gaedike, 1997 (Infurcitinea), spec. n. juliae Satschkov, 1995 (Infurcitinea), syn. n. of Infurcitinea tauridella Petersen, 1968 vanderwolfi Gaedike, 1997 (Infurcitinea), spec. n.